Pentose Phosphate Pathway and Glutathione System of Red Blood Cells at the Exacerbation of Chronic Cytomegalovirus Infection during Pregnancy - Michael T. Lucenko; Irina A. Andrievskaya (International Journal of Biomedicine, 2017)
Objective: To determine the peculiarities of PPP function and GS activity in RBCs of pregnant women at 28 to 30 weeks of gestation during the exacerbation of chronic CMV infection (CMVI). Methods: The study included 50 pregnant women at 28 to 30 weeks of gestation: 25 CMV-seropositive pregnant women (the main group) with CMVI exacerbation and 25 CMV-seronegative pregnant women (the control group). The two groups were matched in age. We determined the activity of G6PD, GR, GP, and the amount of reduced glutathione and NADP; fatty acid peroxide levels in RBCs; the amount of degenerative forms of RBCs; RBC deformation ability; and indicators of the oxygenated form of hemoglobin and 2,3-DPG. Results: In RBCs of pregnant women with CMVI exacerbation at 28 to 30 weeks of gestation, cytophotometry analysis of blood smears showed a 2.16-times reduction in the intensity of histochemical reaction to G6P (P<0.001), a 3.3-times reduction in the intensity of histochemical reaction to reduced glutathione (P<0.001), and a 3.1-times reduction in the intensity of histochemical reaction to reduced NADP (P<0.001), compared with the control group. There were disorders in functioning and structural equivalence in both the disulfide reductase system and oxidative systems of PPP in RBCs, which was reflected in lower activity of GR and GP, 1.9 times (P<0.001) and 2.5 times (P<0.001), respectively, in the main group. At the same time, the content of 2,3-DPG was 1.24 times more (P<0.001), whereas RBC deformability was 2.25 times less than in the control group. Conclusion: CMVI exacerbation at 28 to 30 weeks of gestation causes the inhibition of the metabolic activity of the enzymes of PPP and glutathione system, an initiation of membrane destruction oxidative processes that enhance the deformability of RBCs and decrease oxygen metabolism, which creates the risk of anemia and hemic hypoxia in pregnant women.